The Analysis of SWOT Management and Students’ Interest toward STKIP Muhammadiyah Sungai Penuh - Sakdiah, Halimatus; Arpenas, Arpenas (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
In the Academic Year of 2016-2017, only a few students who enrolled at STKIP Muhammadiyah Sungai Penuh especially on the Physics Education Study Program. This phenomenon was the reason to carry out this research. To overcome this problem, the researchers conducted this qualitative and quantitative research through the use of a questionnaire and validated documents. Samples were selected and taken through random sampling technique. The result of the questionnaire was used to observe the interest of high school students in continuing their education than used as an external factor in conducting SWOT analysis. From the results and discussion, it can be concluded that 1) STKIP Muhammadiyah Sungai Penuh position is in the cell -1 which means it is in a strong market position and highly competitive education industry field. 2) STKIP Muhammadiyah will be more advanced if evaluation and implementation of long term and short term strategies are conducted continuously. 3) Based on the percentage obtained, high school students’ interest in continuing education to college is high, reaching 80%. However, the interest to continue their education to STKIP Muhammadiyah is only 73.1% and the interest in Physics Education Study Program is only 59.1% and 4) students’ interest in continuing education is influenced by several factors such as motivation and aspirations, interest, parents, peers, siblings and school environment.